Clinical utility of minimally invasive posterior internal fixation within the pelvic ring using S2 alar iliac screws for unstable pelvic ring fracture. Issue 10 (October 2022) - Wakayama, Yusuke; Higashi, Takayuki; Kobayashi, Naomi; Choe, Hyonmin; Matsumoto, Masahiro; Abe, Takeru; Takeuchi, Ichiro; Inaba, Yutaka
Highlights: Internal fixation for unstable pelvic ring fractures is associated with complications, including bleeding, invasion of soft tissues, and a weak fixation force. This study compared surgical outcomes of internal fixation within the pelvic ring using the S2 alar iliac screw with trans-iliac plate fixation. Internal fixation in the pelvic ring using the S2 alar iliac screw is a less invasive technique, with less intraoperative bleeding, than trans-iliac plate fixation. Abstract: Introduction: Posterior internal fixation for unstable pelvic ring fractures is often associated with complications, including pelvic hemorrhage and gluteal necrosis. Pelvic ring fixation using the S2 alar iliac screw (SAIS) without fixation of the lumbosacral vertebrae may have potential as a novel, minimally invasive technique for treating unstable pelvic ring fractures. The present study compared clinical outcomes in patients who underwent SAIS fixation within the pelvic ring with a historical control group of patients who underwent conventional trans-iliac plate fixation for the treatment of unstable pelvic ring fractures. Materials and methods: Thirty-two patients diagnosed with unstable pelvic fractures with sacral fracture or sacroiliac joint fracture dislocation were retrospectively evaluated. Eight consecutive patients underwent trans-iliac plate fixation from April 2012 to March 2015, and 24 consecutive patients underwent SAIS fixation from April 2015 to February 2020. Rates of soft tissue complications, intraoperative blood loss, and intraoperative blood transfusion volume were compared in these two groups. Results: Mean intraoperative blood loss was significantly lower in patients who underwent SAIS fixation than in those who underwent trans-iliac plate fixation (141.0 ml vs 315.0 ml; P  = 0.027), although there were no between-group differences in intraoperative blood transfusion volume (0.0 ml vs 140 ml; P  = 0.105), incidence rate of soft tissue complications (4.2% vs 0%; P  = 1.000), and operation time (88.5 min vs 93.0 min; P  = 0.862). Bone healing was confirmed in all patients who underwent SAIS fixation without dislocation of the fracture site, whereas one patient who underwent trans-iliac plate fixation experienced a dislocation of the fracture site during follow-up (0% vs 12.5%; P  = 0.250). Conclusions: SAIS fixation reduces intraoperative blood loss and ensures bone healing without major complications, including dislocation of the fracture site. SAIS fixation may therefore be an alternative, minimally invasive method of treating unstable pelvic fractures.